Implementation Of The Evaluation Of The Volume Of Maximum Oxygen Uptake (Vo2 Max) Athletes Koni Rokan Hulu - Ridwan Sinurat (Universitas Negeri Padang Press, Pusat Kajian Pendidikan Olahraga, Kesehatan dan Rekreasi, Fakultas Ilmu Keolahragaan, Univeristas Negeri Padang., 2021)
The quality of maximum oxygen volume (VO2max) for athletes is important for an athlete's performance. VO2Max is the maximum volume of oxygen that can be used per minute. The maximum amount of oxygen consumed per unit time by a person during exercise or tests, with training progressively heavier until exhaustion, is called VO2Max. The Vo2Max Direct examination is the most accurate test in determining the level of heart and lung fitness in performing physical activities with maximum intensity. Maximum oxygen uptake (Vo2max) is defined as the maximum value at which oxygen can still be taken, distributed, and used by the body when the intensity of physical activity reaches its maximum. This service method provides material on the importance of evaluating physical conditions, especially Vo2max to athletes. This service aims to help the Indonesian National Sports Committee (KONI) Rokan Hulu Regency to find out the fitness of athletes from several sports as seen from VO2 Max. The method used in this service is that all athletes follow the service's direction about the importance of VO2 Max and perform a Multistage Fitness Test (MFT). The results of this dedication by the athletes and management of KONI understand the importance of VO2 Max and the results of the MFT test, only a few athletes in good and other categories are sufficient and low.